Kontribusi Pendapatan Wanita Peternak Itik Terhadap Pendapatan Keluarga Di Desa Bate Puteh Kecamatan Langsa Lama Kota Langsa Aceh, Indonesia: The Contribution of Female Duck Farmers to Family Income in Bate Puteh Village, Langsa Lama District, Langsa City, Aceh, Indonesia (Jurnal Riset Agribisnis dan Peternakan, 2025)
This study aims to analyze the contribution of income and working time allocation of women duck farmers in Batee Puteh Village, Langsa Lama District, Langsa City, Aceh, in supporting family income. The sampling technique used is Saturated Sampling, with a total of 12 women duck farmers as the sample. The data utilized in this research consist of primary and secondary data. The data analysis methods employed are income analysis and the Harvard analysis framework. The results of the study indicate that the average total working hours of women duck farmers across all activities is 11.66 hours per day, or 48.58%, with a rest time of 12.33 hours per day. The income earned by women broiler duck farmers amounts to IDR 9,250,818 per year or IDR 793,401 per month, while the income of women laying duck farmers amounts to IDR 1,715,513 per year or IDR 142,959 per month. Women broiler duck farmers contribute 18%, and women laying duck farmers contribute 10.25% to family income. This contribution percentage is categorized as low based on the contribution interval scale. Hypothesis testing reveals that the contribution of women duck farmers to family income is 22%, which falls into the low category. The production activities are dominated by women, reproductive activities are also dominated by women, while social and community activities are shared equally by both genders.
Keywords: Contribution; Duck Farmers; Income; Women